Novel anti-inflammatory and analgesic agents: synthesis, molecular docking and in vivo studies - David Izuchukwu Ugwu; Uchechukwu Christopher Okoro; Pius Onyeoziri Ukoha; Astha Gupta; Sunday N. Okafor (Taylor & Francis Group, 2018)
Twelve new derivatives of benzothiazole bearing benzenesulphonamide and carboxamide were synthesised and investigated for their in vivo anti-inflammatory, analgesic and ulcerogenic activities. Molecular docking showed an excellent binding interaction of the synthesised compounds with the receptors, with 17c showing the highest binding energy (-12.50 kcal/mol). Compounds 17c and 17i inhibited carrageenan-induced rat paw oedema at 72, 76, and 80% and 64, 73, and 78% at 1 h, 2 h, and 3 h, respectively. In the analgesic activity experiment, compounds 17c, 17 g, and 17i had ED50 (µM/kg) of 96, 127, and 84 after 0.5 h; 102, 134, and 72 after 1 h and 89, 156, and 69 µM/kg after 2 h, respectively, which were comparable with 156, 72, and 70 µM/kg for celecoxib. The ulcerogenic index of the most active derivatives 17c and 17i were 0.82 and 0.89, respectively, comparable to 0.92 for celecoxib. The physicochemical studies of the new derivatives showed that they will not have oral bioavailability problems.